2019
DOI: 10.3390/met9121326
|View full text |Cite
|
Sign up to set email alerts
|

Study on Short-Circuiting GMAW Pool Behavior and Microstructure of the Weld with Different Waveform Control Methods

Abstract: In order to study internal relation among the behavior of the weld pool, the microstructure of weld bead and the waveform of short-circuiting gas metal arc welding (S-GMAW), a high speed photograph-images analysis system was formed to extract characteristics of weld pool behavior. Three representative waveform control methods were used to provide partly and fully penetrated weld pools and beads. It was found that the behavior of the weld pool was related to the instantaneous power density of the liquid bridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The benefits of this technique include the possibility of manufacturing large size details with a significantly high accuracy and a high layer deposition rate in a controlled protective gas environment, which increases the quality of the formed structure. Two known variations of gas metal arc welding are most commonly employed in industrial applications-cold metal transfer (CMT) and cold arc pulse [11][12][13][14]. These studies indicate that the two methods are similar in that they strive to achieve the same goal through two slightly different approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of this technique include the possibility of manufacturing large size details with a significantly high accuracy and a high layer deposition rate in a controlled protective gas environment, which increases the quality of the formed structure. Two known variations of gas metal arc welding are most commonly employed in industrial applications-cold metal transfer (CMT) and cold arc pulse [11][12][13][14]. These studies indicate that the two methods are similar in that they strive to achieve the same goal through two slightly different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The high controllability of the two processes is what makes them ideal for automation and integration in complicated mechatronic devices such as fully automated robotic systems. The pulsing nature of the welding process leads to the formation of a smaller heat affected zone, which intern allows for the employment of the two methods for the welding of thin metal sheets, as well as light metal components such as aluminum which has one of the lowest melting temperatures amongst other metals [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The metal vapor and photoinduced plasma are highintensity interference light sources, which are difficult to achieve the ideal effect when shooting keyhole directly. Previous literature [27,35,43,44]and our attempts have shown that the use of lasers with a center wavelength of about 1070 nm and austenitic stainless steel, narrow band filters around 808 nm and auxiliary illumination lasers of the same wavelength can well suppress interference of photo-induced plasma and spatter. Due to the non-coaxial imaging configuration, the reflected light on the surface of the base material has little effect on the imaging and can be ignored.…”
Section: A the Architecture Of Welding Systemmentioning
confidence: 83%
“…To describe the nature of the arc burning, its stability, as well as identifying characteristic zones during arc burning (AEA-arc extinction area; SCA-short-circuiting area; ABA-arc burning area), the use of current and voltage cyclograms has become widespread [86,91,93]. Current and voltage cyclograms show welding voltage as a function of the welding current.…”
Section: Current and Voltage Cyclogramsmentioning
confidence: 99%